2007
DOI: 10.1111/j.1471-4159.2007.04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical modulation of short‐term facilitation of dopamine release by dopamine autoreceptors

Abstract: Electrophysiological studies have demonstrated that dopaminergic neurons burst fire during certain aspects of rewardrelated behavior; however, the correlation between dopamine release and cell firing is unclear. When complex stimulation patterns that mimic intracranial self-stimulation were employed, dopamine release was shown to exhibit facilitated as well as depressive components (Montague et al. 2004). Understanding the biological mechanisms underlying these variations in dopamine release is necessary to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 57 publications
(80 reference statements)
6
57
1
Order By: Relevance
“…Similarly, the stimulation of D 2 , but not D 1 , DA receptors induced a marked increase in FGF-2 expression in the striatum and cortex (Roceri et al, 2001;Fumagalli et al, 2003). The present study also showed that D 1 DA (Kita et al, 2007) demonstrate that D 2 receptors provide a presynaptic component that can not only modulate autoinhibition, but also short-term facilitation of DA release, therefore impacting both D 1 -and D 2 -mediated postsynaptic plasticity. As for how D 2 signal transduction mechanisms modulate FADD activation, it has been previously described that activation of the D 2 receptors can activate ERK (Luo et al, 1998;Yan et al, 1999) and also that FADD modulation by opiate drugs was dependent on the activation of the antiapoptotic ERK1/2 signaling pathway (Garcia-Fuster et al, 2007), which suggests ERK as a possible mediator of FADD modulation after D 2 receptor activation by cocaine.…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Alsupporting
confidence: 51%
“…Similarly, the stimulation of D 2 , but not D 1 , DA receptors induced a marked increase in FGF-2 expression in the striatum and cortex (Roceri et al, 2001;Fumagalli et al, 2003). The present study also showed that D 1 DA (Kita et al, 2007) demonstrate that D 2 receptors provide a presynaptic component that can not only modulate autoinhibition, but also short-term facilitation of DA release, therefore impacting both D 1 -and D 2 -mediated postsynaptic plasticity. As for how D 2 signal transduction mechanisms modulate FADD activation, it has been previously described that activation of the D 2 receptors can activate ERK (Luo et al, 1998;Yan et al, 1999) and also that FADD modulation by opiate drugs was dependent on the activation of the antiapoptotic ERK1/2 signaling pathway (Garcia-Fuster et al, 2007), which suggests ERK as a possible mediator of FADD modulation after D 2 receptor activation by cocaine.…”
Section: Regulation Of Fadd By Cocaine M-j García-fuster Et Alsupporting
confidence: 51%
“…Consistent with this hypothesis, disulfiram-induced increase in extracellular DA was reversed in both cortices by the local perfusion of the sodium channel inhibitor TTX, confirming that DA was released via a nerve impulse mediated exocytotic process, as well as by the systemic administration of clonidine, consistent with the ability of α 2 -agonists to suppress noradrenergic activity (Svensson et al 1975), but was not reduced by the D 2 agonist quinpirole, in spite of its ability to inhibit dopaminergic activity (White and Wang 1984;Kita et al 2007). …”
Section: Discussionmentioning
confidence: 80%
“…Repeated-burst stimulation of the MFB at frequencies of 20 to 50 Hz facilitates DA overflow in the dorsal striatum in mice and rats in such a way that more DA is released after subsequent stimuli than that observed after the first stimulus (Yavich, 1996;Yavich and MacDonald, 2000;Kita et al, 2007). A working model shown in Fig.…”
Section: Resultsmentioning
confidence: 99%